2019
DOI: 10.1200/jco.2019.37.15_suppl.3503
|View full text |Cite
|
Sign up to set email alerts
|

Association of colon cancer (CC) molecular signatures with prognosis and oxaliplatin prediction-benefit in the MOSAIC Trial (Multicenter International Study of Oxaliplatin/5FU-LV in the Adjuvant Treatment of Colon Cancer).

Abstract: 3503 Background: MOSAIC and C-07 showed that oxaliplatin (OX) added to 5-fluorouracil plus leucovorin significantly improved disease free survival (DFS). However, OX is associated with neurotoxicity and the vast majority of patients do not receive OX-benefit; highlighting the importance of an OX-benefit predictor. In C-07, colon tumors with a CRCA (Colorectal Cancer Assigner) stem-like subtype were associated with a poor prognosis and no OX-benefit, but stage III patients with an enterocyte subtype did. We te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…However, the results were not significant in terms of benefit with oxaliplatin in the CMS2 population. 57 …”
Section: Cms: a Multilevel Crc Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results were not significant in terms of benefit with oxaliplatin in the CMS2 population. 57 …”
Section: Cms: a Multilevel Crc Classificationmentioning
confidence: 99%
“…However, the results were not significant in terms of benefit with oxaliplatin in the CMS2 population. 57 In the metastatic setting, retrospective analyses of large clinical trials have been conducted to investigate an association between CMS groups and activity of cetuximab or bevacizumab. Both the CALGB-80405 and FIRE3 trials reported poor survival for patients with CMS1 tumors, intermediate survival for CMS4, and good outcomes associated with CMS2 across the two treatment arms.…”
Section: Figurementioning
confidence: 99%
“…Oppositely, prognostic associations in the early and/or metastatic setting were found for both CMS and pre-consensus classifications including CRCA subtypes. [12][13][14]20 We therefore investigated whether gene expression subtypes could predict the benefit from two treatment strategies, rather than from individual targeted agents, with the hypothesis that an intensified upfront treatment could be especially useful for subtypes with poor prognosis. In order to focus on a homogeneous series, we selected only chemotherapy-naive primary tumors for our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…oxaliplatin, used in the vast majority of patients included in the CALGB study, is limited to tumors with a fibroblast-low microenvironment (CMS2/3). In this context, it is important to note inconsistent results in studies assessing CMS groups as predictors of benefit with oxaliplatin and irinotecan in the early-stage and metastatic settings, respectively [11,12]. In practice, the independent versus combinatorial effect of different chemotherapy agents and targeted drugs in the CMS framework is difficult to disentangle.…”
Section: Annals Of Oncologymentioning
confidence: 99%
“…In order to better exploit CMS for therapy selection, we should exit the paradigm of CMS as a 'one marker fits all' tool to optimize the use of existing drugs. Different research groups are actively working to refine the transcriptomic analysis of CRC from the viewpoint of treatment efficacy prediction, such as the combination of CMS classification with a signature of DNA damage repair efficiency to model oxaliplatin benefit in the adjuvant setting [11]. The CMS classification should be a starting point to deepen our knowledge about CRC biology and the 'drivers' of metastatic progression that could support drug discovery and rational combination therapies.…”
Section: Annals Of Oncologymentioning
confidence: 99%